PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE BRAINSTORMING DI SMK AGAPE PATRIA SOSOK - Yosepha, Yosepha; Hanye, Paternus; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSpeaking is one of the skills taught in Indonesian language subjects in schools. A teacher must be able to determine the right strategy or learning method to improve learning outcomes. One of the methods that could be applied is brainstorming. The use of brainstorming method in the learning process could foster students’ enthusiasm and interest in learning. The students were required to actively seek and find the learning by identifying, collecting the data, testing the validity of data, and concluding the data. The method used in this research was descriptive method with qualitative research form which the data obtained in the form of numbers that would be described. The type of research was classroom action research which had been done in two cycles. The subject of the research was Indonesian language teacher and the students of class IX AP that contained 22 students. The result of the data analysis before the method was implemented was 69.54. In the Cycle 1, the improvement of students’speaking skill after using brainstorming method was 76.36. In the Cycle 2, the students’ score increased into 79.54. As a conclusion, the students’ speaking skill from cycle to cycle was improved significantly by implementing brainstorming method.   Keywords: Speaking skills, Negotiating, Brain-storming Methods